OMNIBUS LAW IMPACT ON WORKER WELFARE IS UNCERTAIN - Achmad zahruudin; Yahman Yahman; Dudik Djaja Sidarta; Arman Paramansyah; Loso Judijanto (Faculty of Law, Universitas Pekalongan, 2023)
The Omnibus Law, also known as the Omnibus Law , is a progressive step taken by the government in the legal sector. Its purpose is to eliminate overlaps and conflicts between laws and regulations in similar sectors by reorganizing them. The legal protection of workers' normative rights in the Omnibus Law will also be analyzed. This thesis aims to examine the regulation of normative rights of workers in the Omnibus Law and compare its strengths and weaknesses to Law Number 13 of 2003. The research method used is normative juridical legal research, which involves referring to legal norms and researching library materials or secondary materials. This includes processing data from primary legal materials, secondary legal materials, and tertiary legal materials. The research results indicate that the Omnibus Law regulates normative labor rights to protect workers, as stated in Article 80. This article aims to strengthen worker protection, increase their role, and improve their welfare in supporting the investment ecosystem. The Omnibus Law is weaker than Law Number 13 of 2003 in terms of regulating the normative rights of workers. It is considered detrimental to workers and lacks legal protection for their normative rights. The only provides limited protection for workers' rights through Article 81, which is related to employment. Legal protection should guarantee workers' rights, as outlined in Law Number 11 of 2020 concerning Job Creation